2001
DOI: 10.1136/oem.58.6.399
|View full text |Cite
|
Sign up to set email alerts
|

Short term respiratory effects of acute exposure to chlorine due to a swimming pool accident

Abstract: Objective-Acute exposure to chlorine causes lung damage, and recovery may proceed slowly for several weeks. The short term respiratory eVects of acute chlorine inhalation during a swimming pool accident were examined. Methods-A total of 282 subjects (134 children, aged <14 years) inhaled hydrogen chloride and sodium hypochlorite during an accident caused by a malfunction of the water chlorinating system in a community pool in Rome in 1998. Most people received bronchodilators and cortisone at the emergency roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 21 publications
3
43
0
2
Order By: Relevance
“…Acute exposure to high levels of chlorine gas, resulting from explosions, leaks or malfunctioning of chlorine-disinfection installations [12][13][14] is a wellknown problem. The health consequences of such incidents may be more or less serious.…”
Section: Acute Hazards Related To the Chlorination Of Swimming Poolsmentioning
confidence: 99%
“…Acute exposure to high levels of chlorine gas, resulting from explosions, leaks or malfunctioning of chlorine-disinfection installations [12][13][14] is a wellknown problem. The health consequences of such incidents may be more or less serious.…”
Section: Acute Hazards Related To the Chlorination Of Swimming Poolsmentioning
confidence: 99%
“…20 There are studies investigating the effects of acute chlorine exposure especially on children. Agabiti et al 21 examined the short-term respiratory effects of acute chlorine inhalation as a result of a swimming pool accident in 282 cases, 134 of them children: they reported that persistent symptoms and lung function impairment were found up to 1 month after the incident. They also reported that, among the children involved, the incidence of all symptoms tended to be higher in those who had a history of chronic respiratory disease 21 .…”
Section: Respiratory Effects Of Acute Chlorine Exposurementioning
confidence: 99%
“…Because, for the AF in our case there was no predisposing factor or structural cardiac abnormality. Following exposure to chlorine gas, the cases respond differently to the administered treatment, this was explained by the differences in the duration of exposure, the presence of underlying systemic diseases and chronic repiratory diseases [12,16]. The cases are frequently discharged within 48 hours [17], however there might be persistent or delayedonset symptoms.…”
Section: Discussionmentioning
confidence: 99%